A systematic review of the association between neighborhood physical disorder and individual health - Huimin Zhao; Yue Ma; Ningrui Liu; Ying Long (Discover Cities)
Abstract Neighborhood physical disorder (NPD) has been theorized to be associated with health outcomes at an individual level, with inconsistent evidence across studies. To address these discrepancies, a systematic review is imperative to unravel the discrepancies present in the literature and offer an evidence-based assessment of the association between NPD and individual health. This systematic review analyzed 50 studies that adhered to the inclusion criteria out of the 4185 articles retrieved. The majority of the studies included in this review were conducted in the United States and employed cross-sectional designs. The measurement of NPD predominantly relied on traditional methods, such as interview or questionnaire, and most studies focus on individuals’ physical health and health-related behaviors, with relatively less attention paid to mental health, social health and self-rated health. Findings from the systematic review revealed that 20 cross-sectional studies showed a correlation, while 17 did not. Additionally, 10 cohort studies identified an adverse effect of NPD on health outcomes, whereas 8 cohort studies and 1 case–control study reported null findings. Subgroup analysis showed that the diversity of NPD types, variations in the indicator systems employed, and disparities in the definition of the neighborhood contributed to the heterogeneity of findings.